How to apply makeup

By applying a base coat material with reactive silyl groups and specific powders to deteriorated wall surfaces, the method addresses issues of blistering and peeling, ensuring a durable and aesthetically pleasing finish on uneven wall surfaces.

JP7618074B2Active Publication Date: 2025-01-20BEKKU KK
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024002456
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-31
Filing Date
2024-01-11
Publication Date
2025-01-20
Estimated Expiration
2040-07-31

AI Technical Summary

Technical Problem

Existing methods for applying coatings to deteriorated wall surfaces with uneven patterns, such as those made of plate-shaped materials, often result in issues like blistering and peeling over time, leading to unsatisfactory durability and aesthetic degradation.

Method used

A method involving the sequential application of a base coat material and a top coat material, where the base coat includes a resin component with reactive silyl groups and specific powders, is used to enhance adhesion and durability on existing wall surfaces with uneven patterns.

Benefits of technology

The method effectively forms a beautiful and durable new coating that maintains its appearance for a long time by improving adhesion and resistance to environmental factors, even on surfaces with irregular patterns.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618074000001
    Figure 0007618074000001
  • Figure 0007618074000002
    Figure 0007618074000002
  • Figure 0007618074000003
    Figure 0007618074000003
Patent Text Reader

Abstract

To provide a decoration method capable of forming an aesthetically pleasing, newly deposited coating film and holding its finished state over a long period on an existing wall surface having an uneven pattern and comprising an existing coating film of high durability.SOLUTION: The present invention is a decoration method for an aged existing wall surface, the existing wall surface having an uneven pattern on its surface and comprising at least one type of existing coating film selected from an inorganic coating film, an organic-inorganic composite coating film and a fluorine resin coating film. To the existing wall surface is applied an under coating containing a resin component and powder (m) of an average particle diameter equal to or less than 1 μm and / or powder (n) with an oil absorption amount equal to or higher than 100 ml / 100 g and an average particle diameter of 2-100 μm, where a total amount of the powder (m) and the powder (n) is 10-250 pts.wt. relative to a solid content of the resin component 100 pts.wt., and a pigment volume concentration is 1-30%. After drying the coating, an upper coating is applied.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a decorative method that can be applied to buildings and the like. [Background technology]

[0002] Conventionally, concrete, mortar, various plate-shaped wall materials, etc. have been used for the walls of buildings, etc. Among these, for example, plate-shaped wall materials that have been provided with a concave-convex pattern on their surfaces to give them a three-dimensional appearance and that have been coated for protection and beauty purposes are often used. Materials that are used for such coatings are preferably those that can form highly durable coatings, such as inorganic coatings, organic-inorganic composite coatings, and fluororesin coatings, from the viewpoints of extending life and reducing maintenance.

[0003] Since a wall surface made of such a plate-like wall material is exposed to the outdoors for a long period of time, the surface of the plate-like wall material deteriorates due to the effects of sunlight, rainfall, temperature changes, dust, etc., and the initial aesthetic appeal of the plate-like wall material decreases over time. Even in a wall surface provided with a highly durable coating, it is difficult to avoid deterioration and loss of aesthetic appeal over time.

[0004] Japanese Patent Application Laid-Open No. 2016-117795 describes the application of an undercoat paint containing an epoxy resin, an amine compound, a silane coupling agent, etc. to a coating of an acrylic silicone resin, etc. The patent publication shows that such an undercoat paint exhibits good adhesion to a highly durable coating of an acrylic silicone resin, etc. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2016-117795 A Summary of the Invention [Problem to be solved by the invention]

[0006] However, even if the deteriorated surfaces of plate-like wall materials having uneven patterns are dressed using the methods described in the above patent documents, there is a risk of swelling, peeling, etc. occurring over time, making it difficult to obtain practically satisfactory results.

[0007] The present invention has been made in consideration of the above-mentioned problems, and aims to provide a decorative method that can form a beautiful new coating on an existing wall surface having a rough pattern and a highly durable existing coating, and can maintain the finished state for a long period of time. [Means for solving the problem]

[0008] As a result of intensive research into achieving the above-mentioned object, the inventor came up with the idea of ​​a method of applying a specific undercoat material and a topcoat material in sequence to an existing wall surface as described above, and completed the present invention.

[0009] That is, the present invention has the following features. 1. A decorative method for existing walls that have deteriorated over time, The existing wall surface has an uneven pattern on its surface. The present invention provides a method for manufacturing a steel sheet having at least one existing coating selected from an inorganic coating, an organic-inorganic composite coating, and a fluororesin coating, For the above existing wall, A resin component, and a powder (m) having an average particle diameter of 1 μm or less and / or a powder (n) having an oil absorption of 100 ml / 100 g or more and an average particle diameter of 2 to 100 μm, the resin component includes a compound having a reactive silyl group, the compound having a reactive silyl group being one or more selected from a tetraalkoxysilane compound, an alkylalkoxysilane compound, and a silane coupling agent; The powder (n) is one or more selected from zeolite, sodium sulfate, alumina, allophane, diatomaceous earth, hydrous silicon dioxide, vermiculite, perlite, Oya stone powder, activated clay, charcoal, activated carbon, wood powder, and shirasu balloon; The total amount of the powder (m) and the powder (n) is 10 to 250 parts by weight per 100 parts by weight of the solid content of the resin component, and a primer having a pigment volume concentration of 1 to 30% is applied, and after the coating is dried, a topcoat material is applied. This is a cosmetic method characterized by the above. The oil absorption amount is a value measured by the method of JIS K5101-13-1:2004 "Refined linseed oil method". 2. The decorative method described in 1, wherein the existing wall surface has an uneven pattern on its surface and is composed of a plurality of plate-shaped wall materials provided with an existing coating. Effect of the Invention

[0010] According to the present invention, a beautiful new coating can be formed on an existing wall surface having an uneven pattern and an existing coating, and the finished state can be maintained for a long period of time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described.

[0012] The present invention can be applied to existing wall surfaces of buildings, civil engineering structures, etc. Such existing wall surfaces are composed of at least a substrate and an existing coating. Examples of the substrate include concrete, mortar, metal, wood, glass, etc., or various plate-shaped wall materials. Examples of the plate-shaped wall materials include inorganic hardened bodies mainly composed of cement, calcium silicate, lime, gypsum, etc. Specific examples of such plate-shaped wall materials include cement boards, extrusion molding boards, slate boards, PC boards, ALC boards, fiber-reinforced cement boards, siding boards, ceramic boards, calcium silicate boards, gypsum boards, and hard wood chip cement boards.

[0013] In the present invention, the existing wall surface is one having a concave-convex pattern on its surface. Various concave-convex patterns on existing wall surfaces can be mentioned, such as tile patterns, brick patterns, geometric patterns, stripes, lattice patterns, polka dot patterns, sand wall patterns, citron skin patterns, ripple patterns, and other patterns that are designed with animals and plants. Specifically, the shape of the convex parts when the concave-convex pattern is seen from the front can be, for example, a square, a rectangle, a circle, an ellipse, a triangle, a diamond, a polygon, an indefinite shape, and the like. In addition, the cross-sectional shape of the convex parts in the concave-convex pattern can be, for example, a trapezoid, a square, a rectangle, a semicircle, a wave shape, a step shape, a triangle, a mountain shape, and the like. As the concave parts in the concave-convex pattern, for example, flat ones that form joints can be mentioned. The height difference between the concave parts and the convex parts can be constant or different in each part, but is preferably 20 mm or less, more preferably about 1 to 15 mm. Such a concave-convex pattern may be applied to either one or both of the substrate and the existing coating.

[0014] In the existing wall surface of the present invention, at least one existing coating selected from an inorganic coating, an organic-inorganic composite coating, and a fluororesin coating (hereinafter also referred to as a "highly durable existing coating") is provided on the surface of the substrate. This existing coating is a highly durable coating that has already been applied to the substrate by on-site painting or factory painting (line painting). Examples of such existing coatings include colored coatings (enamel coatings, printed coatings, etc.), clear coatings, and laminated coatings thereof, which are coatings formed by applying and curing various coating materials to the substrate. Such coating materials may be, for example, any of room temperature drying type, room temperature curing type, bake curing type, ultraviolet (UV) curing type, and electron beam curing type.

[0015] Examples of the binder for such a coating material include inorganic binders such as silicon resin, alkoxysilane, colloidal silica, and silicate, organic-inorganic composite binders such as acrylic silicon resin, and fluororesin.

[0016] The present invention is particularly suitable when the existing coating on the outermost surface is one or more selected from inorganic coatings (coatings containing the above-mentioned inorganic binder), organic-inorganic composite coatings (coatings containing the above-mentioned organic-inorganic composite binder), fluororesin coatings (coatings containing the above-mentioned fluororesin), etc., and can further be suitably applied to these clear coatings. Such existing coatings may contain photocatalytic titanium oxide, etc.

[0017] The present invention can be applied as a remodeling method for the above-mentioned existing wall surface that has deteriorated with age. The degree of deterioration is not particularly limited, but any wall surface that has been used for about 5 years or more (even 8 years or more) can be the subject of the present invention.

[0018] The existing wall surface of the present invention is preferably constructed by arranging a plurality of plate-shaped wall materials having a textured surface and a highly durable existing coating. The present invention can obtain advantageous effects when the existing wall surface is constructed by a plurality of such plate-shaped wall materials. It is desirable that the textured pattern is applied to at least the plate-shaped wall materials themselves. The joints between the plate-shaped wall materials may be filled with a sealant or dry joint material.

[0019] The decorative method of the present invention involves applying (painting) an undercoat material and a topcoat material in that order to an existing wall surface that has deteriorated over time as described above.

[0020] In the present invention, a primer containing a resin component, a powder (m) having an average particle size of 1 μm or less, and / or a powder (n) having an oil absorption of 100 ml / 100 g or more in a specific ratio is used as the primer. In the present invention, the use of such a primer allows the finish state of the new coating formed on the above-mentioned existing wall surface to be maintained for a long period of time.

[0021] As the resin component in the undercoat material, for example, aqueous resins such as water-soluble resins and water-dispersible resins, non-aqueous resins such as solvent-soluble resins and non-water-dispersible resins, or solventless resins can be used.

[0022] Among these, when using aqueous resin as resin component, it is possible to obtain an aqueous undercoat material. The aqueous undercoat material contains water as a medium, and may further contain water-soluble solvent such as lower alcohol, polyhydric alcohol, ether compound, ester compound, alkylene oxide-containing compound, etc., as necessary.

[0023] When a non-aqueous resin is used as the resin component, a non-aqueous undercoat material can be obtained. The non-aqueous undercoat material contains a non-aqueous solvent as a medium. Examples of non-aqueous solvents include aliphatic hydrocarbon solvents such as n-heptane, n-hexane, n-pentane, n-octane, n-nonane, n-decane, n-undecane, and n-dodecane, alicyclic hydrocarbon solvents such as methylcyclohexane and ethylcyclohexane, aliphatic hydrocarbon-containing mixed solvents such as mineral spirits, petroleum solvents such as petroleum ether, petroleum naphtha, solvent naphtha, and kerosene, as well as isoparaffin-based solvents, alcohol-based solvents, ether alcohol-based solvents, ether-based solvents, ester-based solvents, ether ester-based solvents, and ketone-based solvents. These can be used alone or in combination of two or more.

[0024] The non-aqueous undercoat material desirably contains a non-aqueous solvent with an aniline point of 12 to 70°C. It is believed that such a non-aqueous solvent contributes to improving adhesion by slightly swelling or dissolving the existing coating. As a non-aqueous solvent with an aniline point of 12 to 70°C, for example, one or more selected from aliphatic hydrocarbon-containing mixed solvents such as mineral spirits, petroleum ether, petroleum naphtha, solvent naphtha, kerosene, and other petroleum solvents are suitable. The aniline point is a value measured by the method of JIS K2256.

[0025] The resin component in the undercoat material is composed of one or more compounds, and it is desirable that at least one of the compounds is a compound having a reactive silyl group. The resin component in the undercoat material contains a compound having a reactive silyl group as a constituent component, which can further improve the adhesion to existing coatings such as inorganic coatings, organic-inorganic composite coatings, and fluororesin coatings, which is preferable in terms of improving the effects of the present invention. The mechanism of action is not limited to the following, but it is believed that the crosslinking reactivity of the reactive silyl group and the affinity to existing coatings contribute to this.

[0026] The reactive silyl group is, for example, one or more functional groups selected from an alkoxyl group, a hydroxyl group, a phenoxy group, a mercapto group, an amino group, a halogen, etc., bonded to a silicon atom. Among these, an alkoxysilyl group in which an alkoxyl group is bonded to a silicon atom, and / or a silanol group in which a hydroxyl group is bonded to a silicon atom are preferred.

[0027] Examples of compounds having a reactive silyl group include tetraalkoxysilane compounds, alkylalkoxysilane compounds, silane coupling agents, reactive silyl group-containing vinyl compounds, and compounds derived therefrom (e.g., condensates, modified products, polymers, copolymers, etc.). These can be used alone or in combination of two or more.

[0028] Among these, examples of the tetraalkoxysilane compound include tetramethoxysilane, tetraethoxysilane, and tetrabutoxysilane.

[0029] Examples of alkylalkoxysilane compounds include methyltrimethoxysilane, methyltriethoxysilane, methyltributoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, ethyltributoxysilane, propyltrimethoxysilane, propyltriethoxysilane, butyltrimethoxysilane, butyltriethoxysilane, phenyltrimethoxysilane, phenyltriethoxysilane, phenyltributoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, dimethyldibutoxysilane, diethyldimethoxysilane, diethyldiethoxysilane, dipropyldimethoxysilane, dipropyldiethoxysilane, dibutyldimethoxysilane, dibutyldiethoxysilane, diphenyldimethoxysilane, diphenyldiethoxysilane, diphenyldibutoxysilane, methylphenyldimethoxysilane, and methylphenyldiethoxysilane.

[0030] Examples of the silane coupling agent include epoxy group-containing silane coupling agents such as γ-glycidoxypropylmethyldiethoxysilane, γ-glycidoxypropylmethyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino group-containing silane coupling agents such as N-β(aminoethyl)γ-aminopropylmethyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, as well as isocyanate group-containing silane coupling agents, isocyanurate group-containing silane coupling agents, acid anhydride group (carboxyl group)-containing silane coupling agents, and the like.

[0031] Examples of reactive silyl group-containing vinyl compounds include γ-(meth)acryloxypropyltrimethoxysilane, γ-(meth)acryloxypropyltriethoxysilane, γ-(meth)acryloxypropylmethyldimethoxysilane, and γ-(meth)acryloxypropylmethyldiethoxysilane. Such reactive silyl group-containing vinyl compounds can be used in the form of a resin (e.g., acrylic silicone resin, etc.) obtained by copolymerization with other monomers. Examples of such monomers include (meth)acrylic acid alkyl esters, hydroxyl group-containing monomers, carboxyl group-containing monomers, amino group-containing monomers, pyridine-based monomers, nitrile group-containing monomers, amide group-containing monomers, epoxy group-containing monomers, carbonyl group-containing monomers, fluorine-containing monomers, aromatic monomers, ultraviolet absorbing group-containing monomers, and light stable group-containing monomers. These can be used alone or in combination of two or more. In the present invention, acrylic acid alkyl esters and methacrylic acid alkyl esters are collectively referred to as (meth)acrylic acid alkyl esters. The monomer is a general term for a compound having a polymerizable unsaturated double bond.

[0032] The resin component in the undercoat material can contain compounds other than the compound with reactive silyl group. Examples of such compounds include various resins such as acrylic resin, polyester resin, polyether resin, polyurethane resin, fluororesin, vinyl acetate resin, epoxy resin, vinyl chloride resin, etc., or various compounds that can generate these resins.

[0033] As an example of the embodiment of the resin component of the undercoat material, embodiments (1) to (4) are shown below.

[0034] (1) When a resin containing a reactive silyl group-containing vinyl compound in its resin components is used, for example, a resin obtained by copolymerizing at least a reactive silyl group-containing vinyl compound and a hydroxyl group-containing monomer, such a resin can be used in combination with, for example, a polyisocyanate compound (described later) or the like.

[0035] (2) When a resin containing a reactive silyl group-containing vinyl compound in its resin components is used, for example, a resin obtained by copolymerizing at least a reactive silyl group-containing vinyl compound and an epoxy group-containing monomer, such a resin can be used in combination with, for example, a polyamine compound (described later) or the like.

[0036] (3) The resin component in the undercoat material may include an embodiment (3) that includes a polyol compound, a polyisocyanate compound, and a compound having a reactive silyl group.

[0037] Examples of the polyol compound in this embodiment (3) include polyether polyol, polyester polyol, acrylic polyol, polyisoprene polyol, carbonate polyol, etc., and one or more of these can be used. The hydroxyl value of the polyol compound is preferably 10 to 200 KOHmg / g, more preferably 20 to 100 KOHmg / g. The hydroxyl value is a value expressed by mg of potassium hydroxide equivalent to the moles of hydroxyl groups contained in 1 g of resin solid content.

[0038] In the embodiment (3), it is preferable that the polyol compound contains an acrylic polyol (a hydroxyl group-containing acrylic resin). The acrylic polyol can be a polymer of (meth)acrylic acid alkyl ester, a hydroxyl group-containing monomer, and other monomers as necessary, as resin components. The (meth)acrylic acid alkyl ester and the hydroxyl group-containing monomer can be the same as those described above. Examples of the other monomers include carboxyl group-containing monomers, amino group-containing monomers, pyridine monomers, nitrile group-containing monomers, amide group-containing monomers, epoxy group-containing monomers, carbonyl group-containing monomers, alkoxysilyl group-containing monomers, aromatic monomers, ultraviolet absorbing group-containing monomers, and light stable group-containing monomers. These can be used alone or in combination of two or more.

[0039] The polyisocyanate compound has two or more isocyanate groups in one molecule, and crosslinks with the polyol compound to form a polyurethane resin coating. Examples of the polyisocyanate compound include toluene diisocyanate (TDI), 4,4-diphenylmethane diisocyanate (pure-MDI), polymeric MDI, xylylene diisocyanate (XDI), hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI), hydrogenated XDI, hydrogenated MDI, and derivatives thereof (e.g., compounds obtained by urethane reaction, allophanate reaction, isocyanurate reaction, and the like), and those having an allophanate group, those having an allophanate group and an isocyanurate group, and the like can also be used. These can be used alone or in combination of two or more.

[0040] The mixing ratio of the polyisocyanate compound may be set in consideration of the equivalent ratio of the isocyanate group of the polyisocyanate compound to the hydroxyl group of the hydroxyl group-containing resin, i.e., the NCO / OH ratio. The NCO / OH ratio is preferably 0.6 to 1.4, more preferably 0.8 to 1.2. With such a ratio, the effects of the present invention can be sufficiently obtained.

[0041] As the compound having a reactive silyl group in embodiment (3), the same compounds as those mentioned above can be used.

[0042] (4) The resin component in the undercoat material may include an embodiment (4) that includes an epoxy resin, a polyamine compound, and a compound having a reactive silyl group.

[0043] In this embodiment (4), an epoxy resin can be used. Examples of such epoxy resins include flexible epoxy resins and hard epoxy resins. If the epoxy resin contains at least a flexible epoxy resin, this is preferable in terms of improving the effects of the present invention, and advantageous effects can be obtained even in cases where the existing wall surface is one in which a sealant is filled in the joints between plate-like wall materials.

[0044] Examples of flexible epoxy resins include aliphatic modified epoxy resins, butadiene-based epoxy resins, ε-caprolactone modified epoxy resins, thiol-based epoxy resins, amine modified epoxy resins, rubber modified epoxy resins, urethane modified epoxy resins, polyol modified epoxy resins, and fatty acid modified epoxy resins. These can be used alone or in combination of two or more. Among these, fatty acid modified epoxy resins are preferred.

[0045] The ratio of the flexible epoxy resin in the epoxy resin of embodiment (4) (calculated as solid content) is preferably 50% by weight or more, more preferably 70 to 100% by weight, from the viewpoints of adhesion to the base, conformability, and the like.

[0046] The fatty acid modified epoxy resin is obtained by addition reaction of an aliphatic polybasic acid compound to an epoxy resin. For the addition reaction, for example, an esterification reaction can be used. As the epoxy resin used here, for example, bisphenol A type epoxy resin, bisphenol F type epoxy resin, and various epoxy resins such as those exemplified in the hard epoxy resin described below can be used. As the aliphatic polybasic acid compound, for example, maleic acid, maleic anhydride, fumaric acid, itaconic acid, itaconic anhydride, citraconic acid, tetrahydrophthalic acid, tetrahydrophthalic anhydride, hexahydrophthalic acid, hexahydrophthalic anhydride, cyclohexane dicarboxylic acid, succinic acid, malonic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, 1,12-docane diacid, dimer acid, etc. can be mentioned. Among these, dimer acid is preferable.

[0047] Dimer acid is a dimer of an unsaturated fatty acid. Examples of unsaturated fatty acids constituting dimer acid include oleic acid, elaidic acid, cetoleic acid, sorbic acid, linoleic acid, linoleic acid, arachidonic acid, soybean oil fatty acid, tall oil fatty acid, and linseed oil fatty acid.

[0048] The dimer acid modified epoxy resin obtained by addition reaction of dimer acid to epoxy resin is suitable as the epoxy resin of undercoat material.The ratio (solid content equivalent) of dimer acid modified epoxy resin in the epoxy resin of undercoat material is preferably 50% by weight or more, more preferably 70-100% by weight, from the viewpoint of adhesion to base, followability, etc.

[0049] Examples of hard epoxy resins include bisphenol type epoxy resins such as bisphenol A type epoxy resins and bisphenol F type epoxy resins, phenol novolac type epoxy resins such as phenol novolac type bisphenol A epoxy resins and phenol novolac type bisphenol F epoxy resins, novolac type epoxy resins such as cresol novolac type epoxy resins and bisphenol A novolac type epoxy resins, alicyclic epoxy resins, hydrogenated bisphenol A type epoxy resins, glycidyl ether type epoxy resins, bisphenol S type epoxy resins, biphenyl type epoxy resins, dicyclo type epoxy resins, naphthalene type epoxy resins, etc. These can be used alone or in combination of two or more.

[0050] The epoxy resin of the embodiment (4) has an epoxy equivalent (per solid content) of preferably 300 to 3000 g / eq, more preferably 400 to 2000 g / eq, even more preferably 450 to 1500 g / eq, and particularly preferably 500 to 1100 g / eq. By having an epoxy equivalent of not less than the above lower limit, it is suitable in terms of conformability to the substrate, adhesion, etc. By having an epoxy equivalent of not more than the above upper limit, it is suitable in terms of blister resistance, adhesion, topcoat suitability, etc. The epoxy equivalent is the value obtained by dividing the molecular weight of the epoxy resin by the number of epoxy groups.

[0051] The polyamine compound in the embodiment (4) has two or more amino groups in one molecule, and forms an epoxy resin coating by crosslinking with the epoxy resin. Examples of the polyamine compound include polyamine compounds such as aliphatic polyamines, alicyclic polyamines, aromatic polyamines, heterocyclic polyamines, aliphatic polyamides, alicyclic polyamides, aromatic polyamides, aliphatic polyamidoamines, alicyclic polyamidoamines, and aromatic polyamidoamines. These can be used alone or in combination. Among these, one or more polyamine compounds selected from aliphatic polyamines, aliphatic polyamides, and aliphatic polyamidoamines can be preferably used.

[0052] Such polyamine compounds have an active hydrogen equivalent (per solid content) of preferably 40 to 200 g / eq, more preferably 50 to 150 g / eq, and even more preferably 60 to 95 g / eq. By having the active hydrogen equivalent within the above range, sufficient effects can be obtained in terms of adhesion, etc. The active hydrogen equivalent is a value obtained by dividing the molecular weight of the polyamine compound by the number of hydrogen atoms in the amino group.

[0053] In the embodiment (4), the epoxy resin and the polyamine compound can be used by setting each material so that the active hydrogen equivalent of the polyamine compound and the epoxy equivalent of the epoxy resin are preferably less than 0.4, more preferably 0.01 to 0.3, even more preferably 0.03 to 0.25, and particularly preferably 0.05 to 0.2, in terms of [active hydrogen equivalent of the polyamine compound / epoxy equivalent of the epoxy resin]. By using a combination of materials that satisfy such conditions as the epoxy resin and the polyamine compound, more preferable effects can be obtained in terms of adhesion and the like.

[0054] The compounding ratio of the epoxy resin and the polyamine compound is preferably set so that [(amount of polyamine compound / active hydrogen equivalent of polyamine compound) / (amount of epoxy resin / epoxy equivalent of epoxy resin)] is 1.0 or less, more preferably 0.2 to 1.0, even more preferably 0.4 to 0.98, particularly preferably 0.6 to 0.95, and most preferably 0.7 to 0.9. The compounding amount and active hydrogen equivalent of the amine curing agent, and the compounding amount and epoxy equivalent of the epoxy resin are all based on the solid content. By the compounding ratio of the epoxy resin and the polyamine compound being below the above upper limit, it is suitable in terms of adhesion, base followability, topcoat material suitability, etc., and by being above the above lower limit, it is suitable in terms of curability, adhesion, etc.

[0055] The compound having a reactive silyl group in the embodiment (4) can be the same as that described above. In the embodiment (4), a silane coupling agent is preferable, and in particular, one or more selected from an epoxy group-containing silane coupling agent and an amino group-containing silane coupling agent can be preferably used.

[0056] In the embodiment (4), the solid weight ratio of the polyamine compound and the silane coupling agent (polyamine compound: silane coupling agent) is preferably 10:90 to 90:10, more preferably 12:88 to 80:20, even more preferably 14:86 to 65:35, and particularly preferably 15:85 to 50:50. By using both components in such a ratio, the adhesion can be further improved. This is particularly suitable for water-based undercoat materials.

[0057] The undercoat material in the present invention is a resin component having a solid content of SiO 2The compound having a reactive silyl group can be contained within a range of preferably 0.1 to 30% by weight, more preferably 0.2 to 25% by weight, and even more preferably 0.3 to 20% by weight in terms of conversion. By the mixing ratio of the compound having a reactive silyl group being within such a range, the adhesion between the existing coating and the undercoat material coating, and the adhesion between the undercoat material coating and the topcoat material coating can be further improved, and it is also suitable in terms of preventing cracking of the undercoat material coating and the topcoat material coating.

[0058] In addition, SiO 2 The conversion is the amount of silica (SiO 2 ) and is expressed as the weight fraction that remains. In general, tetraalkoxysilanes, alkylalkoxysilanes, etc. react with water and undergo a hydrolysis reaction to become silanols, which then undergo a condensation reaction between silanols or between silanols and alkoxy. When this reaction is carried to its ultimate state, silica (SiO 2 ) These reactions are RO(Si(OR) 2 O) n R+(n+1)H 2 O→nSiO 2 +(2n+2)ROH (R represents an alkyl group. n is an integer.) The reaction formula is as follows: 2 The conversion was made based on the amount of remaining silica component according to this reaction formula.

[0059] The undercoat material contains powder (m) having an average particle size of 1 μm or less (hereinafter also referred to as "(m) component") and / or powder (n) having an oil absorption of 100 ml / 100 g or more (hereinafter also referred to as "(n) component"). In the present invention, the use of such an undercoat material makes it possible to maintain the finish state of the new coating formed on the above-mentioned existing wall surface for a long period of time. The reason for this effect is not limited to the following, but it is presumed that the action of the specific powder in the undercoat material gives viscosity to the undercoat material, making it easier for the undercoat material to be applied evenly along the unevenness of the existing wall surface, and further, the strength of the undercoat material coating is increased due to the cohesive force of the specific powder, etc., which improves adhesion to the highly durable existing coating and also improves resistance to various deterioration factors.

[0060] The average particle size of the (m) component is 1 μm or less, preferably 0.1 to 0.9 μm, more preferably 0.2 to 0.8 μm. The (m) component having such an average particle size is considered to contribute to imparting viscosity to the undercoat material due to the large specific surface area of ​​the powder. By having the average particle size of the (m) component be equal to or greater than the above lower limit, the viscosity of the undercoat material can be appropriately controlled, the workability during application of the undercoat material is sufficiently ensured, and the undercoat material is easily applied evenly along the unevenness of the existing wall surface. The average particle size is the average value measured using a laser diffraction type particle size distribution measuring device (measurement conditions are distribution standard: volume, refractive index: 1.60-0.10i).

[0061] As the component (m), various powders can be used without any particular limitations as long as they satisfy the above physical properties. Examples of the component (m) include titanium oxide, zinc oxide, aluminum oxide, magnesium oxide, calcium carbonate, glass powder, hollow resin particles, and various color pigments. These can be used alone or in combination of two or more. The oil absorption of the component (m) is preferably 500 ml / 100 g or less, more preferably 5 to 200 ml / 100 g, and even more preferably 8 to 80 ml / 100 g. The oil absorption is a value measured by the method of JIS K5101-13-1:2004 "Refined linseed oil method".

[0062] The oil absorption of the (n) component is 100ml / 100g or more, preferably 150ml / 100g or more, more preferably 200ml / 100g or more. The upper limit of the oil absorption of the (n) component is preferably 500ml / 100g or less, more preferably 450ml / 100g or less. The (n) component having such an oil absorption is considered to contribute to imparting viscosity to the undercoat material by absorbing the medium and resin components in the undercoat material. By the oil absorption of the (n) component being below the above upper limit, the viscosity of the undercoat material can be appropriately controlled, the workability during the undercoat material painting is sufficiently ensured, and the undercoat material is easily applied evenly along the unevenness of the existing wall surface.

[0063] As the (n) component, the material is not particularly limited as long as it satisfies the above physical properties, and various powders can be used. Examples of the (n) component include zeolite, sodium sulfate, alumina, allophane, diatomaceous earth, hydrous silicon dioxide, vermiculite, perlite, Oya stone powder, activated clay, charcoal, activated carbon, wood powder, and shirasu balloons. These can be used alone or in combination of two or more. The average particle size of the (n) component is preferably 0.5 μm or more, more preferably 1 to 100 μm, and even more preferably 2 to 80 μm.

[0064] The total amount of the (m) and (n) components is 10 to 250 parts by weight, preferably 25 to 220 parts by weight, and more preferably 35 to 200 parts by weight, per 100 parts by weight of the solid content of the resin component. By having the (m) and (n) components mixed in such a ratio, the above-mentioned powder action and the like are fully exerted, and the finished state of the newly installed coating film can be maintained for a long period of time. If the (m) and (n) components mixed in amounts less than the above lower limit, the action of imparting viscosity and improving strength in the undercoat material becomes insufficient, making it difficult to apply the undercoat material evenly, or the adhesion expression becomes insufficient, making it difficult to obtain the effects of the present invention. If the (m) and (n) components mixed in amounts exceeding the above upper limit, it becomes difficult to obtain a viscosity suitable for applying the undercoat material evenly, and the ratio of the resin component becomes relatively low, which may cause insufficient adhesion expression.

[0065] In the primer, one or more types of powder (o) other than the components (m) and (n) (for example, color pigments, extender pigments, etc. that do not satisfy the above physical property values) can also be used, as long as the effects of the present invention are not significantly impaired.

[0066] The total amount of the (m) component, (n) component, and other powders (o) in the undercoat material, that is, the total amount of all powders, is preferably 10 to 250 parts by weight, more preferably 25 to 220 parts by weight, and even more preferably 35 to 200 parts by weight, relative to 100 parts by weight of the solid content of the resin component. In addition, the total amount of the (m) component and the (n) component in the total amount of all powders is preferably 35% by weight or more, more preferably 45% by weight or more, even more preferably 55% by weight or more, and particularly preferably 65 to 100% by weight. Thus, the undercoat material in which the total amount of all powders is within the above range and the (m) component and the (n) component are contained in a high ratio in the total powder is preferable for fully obtaining the effects of the present invention, and is particularly suitable in that a beautiful new coating can be formed while taking advantage of the uneven pattern of the existing wall surface, and the finished state can be maintained for a long period of time.

[0067] When the undercoat material contains pigments such as (m), (n), and (o), the pigment volume concentration of the undercoat material is preferably 1 to 30%, more preferably 3 to 25%, even more preferably 5 to 23%, and particularly preferably 8 to 20%. By having the pigment volume concentration within the above range, it is possible to enhance the effect of forming a primer coating film with excellent adhesion while making use of the shape of the base. The pigment volume concentration is the volume percentage of the pigment contained in the dry coating film, and is a value calculated from the weight parts and specific gravity of the resin component and pigment constituting the undercoat material. The specific gravity of the resin component is 1.

[0068] The undercoat material can contain a thickener. Examples of the thickener include organic bentonite, fine silica, surface-treated calcium carbonate, amide wax, hydrogenated castor oil wax, benzylidene sorbitol, metal soap, oxidized polyethylene, polymerized vegetable oil, polycarboxylic acid amine salt, xanthan gum, guar gum, polyacrylic acid compound, polyvinyl alcohol, polyethylene oxide, urethane-modified polyether compound, etc. These can be used alone or in combination of two or more.

[0069] The amount of thickener mixed (solid content) is preferably 0.1 to 10 parts by weight, more preferably 0.2 to 5 parts by weight, relative to 100 parts by weight of the solid content of the resin component. If the amount of thickener mixed is within such a range, in combination with the action of the above-mentioned (m) component and (n) component, the undercoat material is easily applied evenly along the unevenness of the existing wall surface, sufficient adhesion can be ensured, and the effect of the present invention can be stably obtained.

[0070] The non-volatile content of the undercoat material (at the time of painting) is preferably 30 to 90% by weight, preferably 40 to 80% by weight, more preferably 45 to 75% by weight. By having such a ratio of the non-volatile content of the undercoat material, the effect of evenly applying the undercoat material along the unevenness of the existing wall surface can be improved. The non-volatile content is a value measured by the method of JIS K5601-1-2, the heating temperature is 105 ° C, and the heating time is 60 minutes.

[0071] The undercoat material may contain various components other than the above components as long as the effect of the present invention is not significantly impaired. Examples of such components include aggregates, dyes, dehydrating agents, leveling agents, wetting agents, plasticizers, film-forming assistants, antifreeze agents, preservatives, antifungal agents, anti-algae agents, antibacterial agents, dispersants, defoamers, adsorbents, fibers, crosslinking agents, ultraviolet absorbers, light stabilizers, antioxidants, curing catalysts, etc. Among these, examples of the curing catalyst include organic tin compounds, organic aluminum compounds, organic titanate compounds, acidic compounds, amine compounds, alkaline compounds, etc. The undercoat material of the present invention can be manufactured by uniformly mixing the above various components by a conventional method. The form of the undercoat material can be, for example, a one-component type, a two-component type, or a multi-component type.

[0072] In the present invention, as the undercoat material, a undercoat material that forms a coating film with a different color tone and / or gloss from the existing wall surface can be used. In the present invention, by using such a undercoat material, it is possible to fully confirm that the undercoat material coating is formed evenly along the unevenness of the existing wall surface on the entire uneven pattern of the existing wall surface, that is, on the entire existing wall surface including the concave and convex parts of the concave and convex parts of the concave and convex parts, and the effect of the present invention can be obtained more stably.

[0073] A primer that forms a coating with a different color tone from the existing wall surface may be one that can be visually recognized as having a different color tone from the existing wall surface (primer coating) after application of the primer. For such a primer, the color difference (ΔE) between the existing wall surface and the primer coating is preferably 3 or more, more preferably 5 or more, and even more preferably 10 or more. For an existing wall surface that has multiple areas with different colors (e.g., a spotted pattern, a lattice pattern, etc.), it is sufficient that the primer coating has a different color tone from the color tone of the area that occupies the largest area among those areas.

[0074] The color difference (△E) is a value measured using a colorimeter. Specifically, the L of the existing wall surface and the undercoat coating * Value, a * Value, b *The L value (average value of 10 measurement points) can be calculated using the following formula. * Value, a * Value, b * The value may be measured on a primer coating formed on an existing wall surface. <Formula>△E={(L * 2 -L * 1 ) 2 +(a * 2 -a * 1 ) 2 +(b * 2 -b * 1 ) 2} 0.5 (In the formula, L * 1 , a * 1 , b * 1 are the L of the existing wall * , a * , b * .L * 2 , a * 2 , b * 2 are the L of the primer coating, * , a * , b * )

[0075] The undercoat material that forms a coating with a different gloss from the existing wall surface may be one that can be visually recognized as having a different gloss from the existing wall surface. For such undercoat materials, the difference in gloss between the existing wall surface and the undercoat material coating is preferably 5 or more, more preferably 10 or more, and even more preferably 15 or more. For an existing wall surface that has multiple areas with different gloss, it is sufficient that the gloss of the undercoat material coating is different from the gloss of the area that occupies the largest area among those areas.

[0076] Glossiness is a value measured using a glossmeter. Specifically, it can be calculated from the 60-degree specular glossiness (average value of 10 measurement points) of the existing wall surface and the primer coating. The glossiness of the primer coating can be measured for the primer coating formed on the existing wall surface.

[0077] The color tone and gloss of the undercoat coating can be set, for example, by adjusting the type and ratio of the resin components, the type and ratio of the powder, etc. The gloss can also be adjusted, for example, by compounding two or more types of resins.

[0078] The primer can be applied directly to the existing wall surface, but various pretreatments can be carried out as necessary. Pretreatments include, for example, removing existing coatings that have deteriorated significantly, removing contaminants by high-pressure water washing, repairing with putty or filler, restoring the surface shape, etc. When applying new sealant to an existing wall surface, it is recommended that the primer be applied approximately 2 to 10 days after the sealant has been applied.

[0079] A known painting tool can be used to apply the undercoat material, such as a spray, roller, brush, or trowel. The amount of primer to be applied may be appropriately determined depending on the surface shape of the existing wall surface, the painting equipment to be used, etc., but is preferably 0.03 to 0.5 kg / m 2 , more preferably 0.05 to 0.3 kg / m 2 When painting, the primer can be diluted as needed.

[0080] The viscosity of the undercoat material during painting is preferably 0.1 to 10 Pa·s, more preferably 0.2 to 5 Pa·s. By having the viscosity of the undercoat material within such a range, the effects of the present invention can be stably obtained. The viscosity referred to here is a value obtained by measuring the viscosity at 20 rpm (the indicator value at the fourth rotation) using a BH type viscometer, and the measurement temperature is 23°C.

[0081] The drying time of the undercoat material is preferably 1 hour or more, more preferably about 2 to 200 hours, at room temperature (0 to 40° C.).

[0082] In the present invention, the topcoat material is applied after the above-mentioned undercoat material is applied and dried. As the topcoat material in the present invention, a material that can utilize the uneven pattern of the existing wall surface is suitable. Specifically usable topcoat materials include, for example, transparent topcoat materials and colored topcoat materials. Transparent topcoat materials contain resin components, and the coating exhibits transparency. Transparent topcoat materials may be those that form a colored transparent coating, and such transparent topcoat materials may contain, in addition to the resin components, colored pigments, etc., within the range that does not impair transparency. Colored topcoat materials include those that contain resin components and colored pigments.

[0083] Various resins can be used as the resin component in the topcoat material. Examples of the resin include vinyl acetate resin, polyester resin, alkyd resin, vinyl chloride resin, epoxy resin, acrylic resin, urethane resin, acrylic silicone resin, fluororesin, etc., or composite resins thereof. Among these, one or more types selected from acrylic resin, urethane resin, acrylic silicone resin, fluororesin, etc. are suitable. In addition, the form of such a resin component includes water-soluble resin, water-dispersible resin (resin emulsion), solvent-soluble resin, solventless resin, non-aqueous dispersion resin, powder resin, etc., among which, one or more types selected from water-soluble resin, water-dispersible resin, solvent-soluble resin, and non-aqueous dispersion resin are suitable. In addition, these resin components may have crosslinking reactivity. When a resin component having crosslinking reactivity is used, the durability, water resistance, weather resistance, chemical resistance, adhesion, etc. of the coating can be improved.

[0084] As the coloring pigment, for example, known inorganic coloring pigments, organic coloring pigments, etc. can be used. By appropriately using one or more of these coloring pigments, the topcoat material can be set to the desired color tone. The mixing ratio of the coloring pigment in the coloring topcoat material is preferably 1 to 500 parts by weight, more preferably 5 to 200 parts by weight, and even more preferably 10 to 150 parts by weight, relative to 100 parts by weight of the solid content of the resin component.

[0085] Such a topcoat material may contain various components other than the above-mentioned components, as long as the effect of the present invention is not significantly impaired. Examples of such components include thickeners, film-forming assistants, leveling agents, wetting agents, plasticizers, antifreeze agents, pH adjusters, body pigments, preservatives, antifungal agents, antialgae agents, antibacterial agents, dispersants, defoamers, adsorbents, fibers, crosslinking agents, coupling agents, ultraviolet absorbers, light stabilizers, antioxidants, low-pollution agents, hydrophilizing agents, water repellents, catalysts, solvents, and water. The topcoat material of the present invention can be manufactured by uniformly mixing the above-mentioned resin components, coloring pigments, and the above-mentioned various components as necessary by a conventional method. The form of the topcoat material can be, for example, a one-component type, a two-component type, or a multi-component type of more than one. In addition, the degree of gloss of the topcoat material can be, for example, glossy, 70% gloss, 50% gloss, 30% gloss, matte, etc.

[0086] Specifically, examples of topcoat materials include weather-resistant topcoat paints for architecture (JIS K5658:2010), weather-resistant paints for steel structures (JIS K5659:2008), glossy synthetic resin emulsion paints (JIS K5660:2008), synthetic resin emulsion paints (JIS K5663:2008), multicolored pattern paints (JIS K5667:2003), synthetic resin emulsion pattern paints (JIS K5668:2010), acrylic resin-based non-aqueous dispersion paints (JIS K5670:2008), and high solar reflectance paints for roofs (JIS K5675:2011).

[0087] In painting the topcoat material, a known painting tool can be used. Examples of the painting tool that can be used include a spray, a roller, and a brush. The amount of topcoat applied may be appropriately determined depending on the surface shape of the existing wall, the type of topcoat applied, the type of painting equipment, etc., but is preferably 0.05 to 0.5 kg / m 2 , more preferably 0.1 to 0.4 kg / m 2 When painting, the topcoat material can be diluted as needed.

[0088] In the present invention, one or more types of topcoat materials can be used. When using two or more topcoat materials, it is also possible to finish the exterior with two or more colors by using topcoats with different colors and painting them separately. EXAMPLES

[0089] The following examples will clarify the features of the present invention.

[0090] [Test Example 1] In Test Example 1, the following undercoat materials 1-1 to 1-11 were prepared as undercoat materials, and tests were carried out using these undercoat materials.

[0091] (Undercoat material 1-1) A base material including a non-aqueous dispersion type acrylic polyol {hydroxyl value: 50 KOH mg / g, weight average molecular weight: 70,000, glass transition temperature: 38°C, solid content: 50% by weight, medium: mineral spirits (aniline point: 42°C)}, powder m1 (titanium oxide, average particle size: 0.3 μm, oil absorption: 13 ml / 100 g, specific gravity: 4.2), amide wax, solvent naphtha (aniline point: 13°C), and a silicone-based defoaming agent, A mixture of a polyisocyanate compound (1,6-diisocyanatohexane derivative, solid content: 100% by weight), a tetraalkoxysilane compound (isobutyl alcohol modified tetramethoxysilane condensate), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 14%, non-volatile content of primer: 61% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2(converted), powder amount: 70 parts by weight per 100 parts by weight of solid content of resin component, thickener amount (solid content): 1 part by weight per 100 parts by weight of solid content of resin component.

[0092] (Undercoating material 1-2) A base material including a non-aqueous dispersion type acrylic polyol (same as above), powder m1 (same as above), amide wax, solvent naphtha, and a silicone-based defoaming agent; A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 22%, non-volatile content of primer: 63% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 (converted), powder amount: 120 parts by weight per 100 parts by weight of solid content of resin component, thickener amount (solid content): 0.8 parts by weight per 100 parts by weight of solid content of resin component.

[0093] (Undercoating material 1-3) A base material containing a non-aqueous dispersion type acrylic polyol (same as above), powder n1 (hydrated silicon dioxide, average particle size: 6 μm, oil absorption: 340 ml / 100 g, specific gravity: 2.0), amide wax, solvent naphtha, and a silicone-based defoaming agent, A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 7%, non-volatile content of primer: 59% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 (converted), powder amount: 15 parts by weight per 100 parts by weight of solid content of resin component, thickener amount (solid content): 1.2 parts by weight per 100 parts by weight of solid content of resin component.

[0094] (Undercoating material 1-4) A base material including a non-aqueous dispersion type acrylic polyol (same as above), powder n1 (same as above), amide wax, solvent naphtha, and a silicone-based defoaming agent; A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 13%, non-volatile content of primer: 57% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 (converted), powder amount: 30 parts by weight per 100 parts by weight of solid content of resin component, thickener amount (solid content): 1 part by weight per 100 parts by weight of solid content of resin component.

[0095] (Undercoating material 1-5) A base material including a non-aqueous dispersion type acrylic polyol (same as above), powder n1 (same as above), amide wax, solvent naphtha, and a silicone-based defoaming agent; A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 20%, non-volatile content of primer: 58% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 (converted), powder amount: 50 parts by weight per 100 parts by weight of solid content of resin component, thickener amount (solid content): 0.8 parts by weight per 100 parts by weight of solid content of resin component.

[0096] (Undercoating material 1-6) A base material including a non-aqueous dispersion type acrylic polyol (same as above), powder n1 (same as above), amide wax, solvent naphtha, and a silicone-based defoaming agent; A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 25%, non-volatile content of primer: 58% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 Conversion: Powder amount: 66 parts by weight per 100 parts by weight of solid content of resin component; Thickener amount (solid content): 0.6 parts by weight per 100 parts by weight of solid content of resin component.

[0097] (Undercoat material 1-7) A base material containing a non-aqueous dispersion type acrylic polyol (same as above), powder n2 (hydrated silicon dioxide, average particle size: 10 μm, oil absorption: 310 ml / 100 g, specific gravity: 2.0), amide wax, solvent naphtha, and a silicone-based defoaming agent, A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 25%, non-volatile content of primer: 58% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 Conversion: Powder amount: 66 parts by weight per 100 parts by weight of solid content of resin component; Thickener amount (solid content): 0.6 parts by weight per 100 parts by weight of solid content of resin component.

[0098] (Undercoating material 1-8) A base material including a non-aqueous dispersion type acrylic polyol (same as above), powder m1 (same as above), powder n2 (same as above), amide wax, solvent naphtha, and a silicone-based defoaming agent; A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio 1.0). Pigment volume concentration: 24%, non-volatile content of primer: 58% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 Conversion), powder amount: 50 parts by weight of powder m1 and 40 parts by weight of powder n2 per 100 parts by weight of solid content of resin component, thickener amount (solid content): 0.8 part by weight per 100 parts by weight of solid content of resin component.

[0099] (Undercoating material 1-9) A base material including a non-aqueous dispersion type acrylic polyol (same as above), powder m1 (same as above), amide wax, solvent naphtha, and a silicone-based defoaming agent; A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 14%, non-volatile content of primer: 61% by weight, ratio of compound with reactive silyl group in resin solid content: 3% by weight (SiO 2 (converted), powder amount: 70 parts by weight per 100 parts by weight of solid content of resin component, thickener amount (solid content): 1 part by weight per 100 parts by weight of solid content of resin component.

[0100] (Undercoating material 1-10) A base material containing non-aqueous dispersion type acrylic polyol (same as above), powder o1 (calcium carbonate, average particle size: 6 μm, oil absorption: 20 ml / 100 g, specific gravity: 2.6), amide wax, solvent naphtha, and a silicone-based defoaming agent, A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 7%, non-volatile content of primer: 61% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 Conversion: Powder amount: 20 parts by weight per 100 parts by weight of solid content of resin component; Thickener amount (solid content): 1.5 parts by weight per 100 parts by weight of solid content of resin component.

[0101] (Undercoating material 1-11) A base material containing non-aqueous dispersion type acrylic polyol (same as above), powder O2 (calcium carbonate, average particle size: 24 μm, oil absorption: 20 ml / 100 g, specific gravity: 2.6), amide wax, solvent naphtha, and a silicone-based defoaming agent, A mixture of a polyisocyanate compound (same as above), a tetraalkoxysilane compound (same as above), and a hardener containing mineral spirits (NCO / OH ratio: 1.0). Pigment volume concentration: 7%, non-volatile content of primer: 61% by weight, ratio of compound with reactive silyl group in resin solid content: 0.5% by weight (SiO 2 Conversion: Powder amount: 20 parts by weight per 100 parts by weight of solid content of resin component; Thickener amount (solid content): 1.5 parts by weight per 100 parts by weight of solid content of resin component.

[0102] (Test Example 1-1) ○ Test i A brown ceramic siding board that had deteriorated due to outdoor exposure was prepared as an existing wall surface (it has tile-like convex and concave parts (joints) on the surface, and the convex parts have an irregular uneven pattern, and has an inorganic clear coating as the top coating layer). Primer 1-1 was applied to the entire surface of this existing wall surface at a rate of 0.1 kg / m. 2 The coating of the undercoat 1-1 was significantly different in color from the existing wall surface (color difference 40), and it was easy to confirm that the undercoat coating was formed evenly over the entire uneven pattern of the existing wall surface while making the most of the uneven pattern. Next, the topcoat (light brown acrylic silicone resin paint) was applied at a rate of 0.2 kg / m 2 The test specimens were prepared by spray painting with 100% CO2 and drying and curing for 7 days. The painting and curing processes were all carried out under standard conditions (temperature 23°C, relative humidity 50%).

[0103] The specimens prepared by the above method were exposed for 500 hours using an accelerated weathering tester (Metal Weather; manufactured by Daipura Wintes Co., Ltd.), and the appearance change (floating, peeling state) of the specimen surface was observed. Next, cross-cuts were made in the coating at each part of the uneven pattern with a cutter knife, and tape was attached to the cross-cut parts and peeled off to confirm adhesion. As a result, in Test Example 1-1, there was no appearance change due to the accelerated weathering test, and no peeling was observed in any part.

[0104] ○ Test II As an existing wall surface, a brown ceramic siding board that had deteriorated due to outdoor exposure (having tile-like convex and concave portions (joints) on the surface, with an irregular uneven pattern on the convex portions, and a fluororesin clear coating as the outermost coating) was prepared. Using this existing wall surface, a test specimen was prepared in the same manner as in Test i, and the test was conducted.

[0105] ○ Test III A brown ceramic siding board that had deteriorated due to outdoor exposure was prepared as the existing wall surface (having tile-like convex and concave portions (joints) on the surface, with an irregular uneven pattern on the convex portions, and an acrylic silicone resin colored coating as the top layer). Using this existing wall surface, a test specimen was prepared in the same manner as in Test i, and the test was conducted.

[0106] The test results are shown in Table 1. In Table 1, the condition after the primer coating was classified into four grades (excellent: A>B>C>D: poor): "A" indicates that the color difference between the existing wall surface and the primer coating was 10 or more, or the gloss difference was 15 or more; "B" indicates that the color difference between the existing wall surface and the primer coating was 5 to 10 or less, or the gloss difference was 10 to 15; "C" indicates that the color difference between the existing wall surface and the primer coating was 3 to 5 or less, or the gloss difference was 5 to 10; and "D" indicates that the color difference between the existing wall surface and the primer coating was less than 3 or the gloss difference was less than 5. The evaluation in the accelerated weather resistance test was classified into four grades (excellent: A>B>C>D: poor): "A" indicates that there was no change in appearance and no peeling was observed in any part, and "D" indicates that there was a clear change in appearance or a lot of peeling was observed.

[0107] (Test Example 1-2) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-2 was used instead of Primer 1-1. After Primer 1-2 was applied, the coating of Primer 1-2 was significantly different in color from the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0108] (Test Example 1-3) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-3 was used instead of Primer 1-1. After Primer 1-3 was applied, the coating of Primer 1-3 had a significantly different gloss than the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0109] (Test Example 1-4) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-4 was used instead of Primer 1-1. After Primer 1-4 was applied, the coating of Primer 1-4 had a significantly different gloss than the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0110] (Test Example 1-5) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-5 was used instead of Primer 1-1. After Primer 1-5 was applied, the coating of Primer 1-5 had a significantly different gloss than the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0111] (Test Example 1-6) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-6 was used instead of Primer 1-1. After Primer 1-6 was applied, the coating of Primer 1-6 had a significantly different gloss than the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0112] (Test Example 1-7) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-7 was used instead of Primer 1-1. After Primer 1-7 was applied, the coating of Primer 1-7 had a significantly different gloss than the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0113] (Test Example 1-8) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-8 was used instead of Primer 1-1. After Primer 1-8 was applied, the coating of Primer 1-8 was significantly different in color and gloss from the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0114] (Test Example 1-9) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-9 was used instead of Primer 1-1. After Primer 1-9 was applied, the coating of Primer 1-9 was significantly different in color from the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface while making use of the uneven pattern. The test results are shown in Table 1.

[0115] (Test Example 1-10) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-10 was used instead of Primer 1-1. After Primer 1-10 was applied, the coating of Primer 1-10 had no difference in color from the existing wall surface, and there was also little difference in gloss, so it was not easy to confirm that the primer coating had been formed evenly over the entire uneven pattern of the existing wall surface. The test results are shown in Table 1.

[0116] (Test Example 1-11) A test specimen was prepared and tested in the same manner as in Test Example 1-1, except that Primer 1-11 was used instead of Primer 1-1. After Primer 1-11 was applied, the coating of Primer 1-11 had no difference in color from the existing wall surface, and there was also little difference in gloss, so it was not easy to confirm that the primer coating had been formed evenly over the entire uneven pattern of the existing wall surface. The test results are shown in Table 1.

[0117] Test Examples 1-1 to 1-9 correspond to Examples, and generally showed better results than Test Examples 1-10 and 1-11 (which correspond to Comparative Examples).

[0118] [Table 1]

[0119] [Test Example 2] In Test Example 2, the following base materials Q1 to Q7 and hardeners R1 to R5 were combined to prepare primer materials 2-1 to 2-12, and tests were conducted using these primer materials.

[0120] (Main agent Q1) Epoxy resin A {dimer acid modified epoxy resin solution, solid content: 60% by weight, epoxy equivalent (per solid content): 780 g / eq, medium: mineral spirits (aniline point 42°C) and solvent naphtha (aniline point 13°C)} 75 parts by weight, powder M1 (titanium oxide, average particle size: 0.3 μ The main agent Q1 was prepared by uniformly mixing 18 parts by weight of 1,2-dichloropropanediol (1,2-dichloropropanediol, oil absorption: 13 ml / 100 g, specific gravity: 4.2), 4 parts by weight of solvent naphtha (same as above), and 4 parts by weight of additives (dispersant, thickener, and defoamer) in a conventional manner.

[0121] (Main agent Q2) 62 parts by weight of epoxy resin a (same as above), 30 parts by weight of powder m1 (same as above), 4 parts by weight of solvent naphtha (same as above), and 4 parts by weight of additives (dispersant, thickener, and defoamer) were uniformly mixed in a conventional manner to produce base agent Q2.

[0122] (Main agent Q3) 55 parts by weight of epoxy resin a (same as above), 35 parts by weight of powder m1 (same as above), 6 parts by weight of solvent naphtha (same as above), and 4 parts by weight of additives (dispersant, thickener, and defoamer) were uniformly mixed in a conventional manner to produce base agent Q3.

[0123] (Main agent Q4) 38 parts by weight of epoxy resin a (same as above), 15 parts by weight of powder m1 (same as above), 30 parts by weight of heavy calcium carbonate (specific gravity 2.7), 12 parts by weight of solvent naphtha (same as above), and 5 parts by weight of additives (dispersant, thickener, and defoamer) were uniformly mixed in a conventional manner to produce main agent Q4.

[0124] (Main agent Q5) 65 parts by weight of epoxy resin a (same as above), 29 parts by weight of solvent naphtha (same as above), and 6 parts by weight of additives (thickener and defoamer) were uniformly mixed in a conventional manner to produce base agent Q5.

[0125] (Main agent Q6) 40 parts by weight of epoxy resin a (same as above), 50 parts by weight of solvent naphtha (same as above), and 10 parts by weight of additives (thickener and defoamer) were uniformly mixed in a conventional manner to produce base agent Q6.

[0126] (Main ingredient Q7) 65 parts by weight of epoxy resin A (same as above), 18 parts by weight of powder O1 (calcium carbonate, average particle size: 6 μm, oil absorption: 20 ml / 100 g, specific gravity: 2.6), 12 parts by weight of solvent naphtha (same as above), and 5 parts by weight of additives (thickener and defoamer) were uniformly mixed in a conventional manner to produce base agent Q7.

[0127] (Main ingredient Q8) 60 parts by weight of epoxy resin b {water-based epoxy resin (water dispersion of bisphenol A type epoxy resin), solid content: 45% by weight, epoxy equivalent (per solid content): 510 g / eq, medium: water}, 25 parts by weight of powder m1 (same as above), 3 parts by weight of ether-based solvent, and 2 parts by weight of additives (dispersant, thickener, and defoamer) were uniformly mixed in a conventional manner to produce main agent Q8.

[0128] (Hardening agent R1) Curing agent R1 was produced by uniformly mixing 15 parts by weight of polyamine compound a {aliphatic polyamidoamine, solid content: 100% by weight, active hydrogen equivalent (per solid content): 80 g / eq}, 4 parts by weight of a silane compound {N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane}, 16 parts by weight of an alcohol-based solvent, and 65 parts by weight of solvent naphtha (same as above) in a conventional manner.

[0129] (Hardening agent R2) 15 parts by weight of polyamine compound a (same as above), 16 parts by weight of alcohol-based solvent, and 69 parts by weight of solvent naphtha (same as above) were uniformly mixed in a conventional manner to produce hardener R2.

[0130] (Hardening agent R3) 25 parts by weight of polyamine compound b {aliphatic polyamide amine, solid content: 100% by weight, active hydrogen equivalent (per solid content): 180 g / eq}, 4 parts by weight of silane compound (same as above), 11 parts by weight of alcohol-based solvent, and 60 parts by weight of solvent naphtha (same as above) were uniformly mixed in a conventional manner to produce curing agent R3.

[0131] (Hardener R4) 35 parts by weight of polyamine compound c {water-soluble modified aliphatic polyamine resin, solid content: 80% by weight, active hydrogen equivalent (per solid content): 140 g / eq, medium: water} and 65 parts by weight of the silane compound (same as above) were uniformly mixed in a conventional manner to produce curing agent R4.

[0132] (Hardener R5) 75 parts by weight of polyamine compound c (same as above) and 25 parts by weight of silane compound (same as above) were uniformly mixed in a conventional manner to prepare curing agent R5.

[0133] (Undercoat material 2-1) The above-mentioned base agent Q1 (100 parts by weight) and the above-mentioned curing agent R1 (25 parts by weight) were uniformly mixed to prepare the undercoat material 2-1. The properties of this undercoat material are as shown in Table 1. The compounding ratio of epoxy resin to amine hardener [(amount of polyamine compound / active hydrogen equivalent of polyamine compound) / (amount of epoxy resin / epoxy equivalent of epoxy resin)] (referred to as "compounding ratio" in Table 1) was 0.81. Pigment volume concentration is 8%, The non-volatile content of the primer (referred to as "non-volatile content" in Table 2) was 54% by weight. Ratio of compounds with reactive silyl groups in the resin solids (SiO 2 Conversion, in Table 2, "SiO 2 The equivalent amount is 0.5% by weight. The powder amount is 36 parts by weight per 100 parts by weight of the solid content of the resin component. The amount of thickener (solid content) was 1.6 parts by weight per 100 parts by weight of the solid content of the resin component.

[0134] (Undercoat material 2-2) The above-mentioned base agent Q2 (100 parts by weight) and the above-mentioned hardener R1 (20 parts by weight) were uniformly mixed to prepare the undercoat material 2-2. The properties of this undercoat material 2-2 are shown in Table 2.

[0135] (Undercoat material 2-3) The above-mentioned base agent Q3 (100 parts by weight) and the above-mentioned hardener R1 (18 parts by weight) were uniformly mixed to prepare the undercoat material 2-3. The properties of this undercoat material 2-3 are shown in Table 2.

[0136] (Undercoating material 2-4) The above-mentioned base agent Q2 (100 parts by weight) and the above-mentioned hardener R1 (22 parts by weight) were uniformly mixed to prepare the undercoat material 2-4. The properties of this undercoat material 2-4 are shown in Table 2.

[0137] (Undercoat material 2-5) The above-mentioned base agent Q2 (100 parts by weight) and the above-mentioned hardener R1 (30 parts by weight) were uniformly mixed to prepare the undercoat material 2-5. The properties of this undercoat material 2-5 are shown in Table 2.

[0138] (Undercoat material 2-6) The above-mentioned base agent Q2 (100 parts by weight) and the above-mentioned hardener R2 (20 parts by weight) were uniformly mixed to prepare the undercoat material 2-6. The properties of this undercoat material 2-6 are shown in Table 2.

[0139] (Undercoat material 2-7) The above-mentioned base agent Q2 (100 parts by weight) and the above-mentioned hardener R3 (28 parts by weight) were uniformly mixed to prepare the undercoat material 2-7. The properties of this undercoat material 2-7 are shown in Table 2.

[0140] (Undercoat material 2-8) The above-mentioned base agent Q4 (100 parts by weight) and the above-mentioned hardener R3 (16 parts by weight) were uniformly mixed to prepare the undercoat material 2-8. The properties of this undercoat material 2-8 are shown in Table 2.

[0141] (Undercoat material 2-9) The above-mentioned base agent Q5 (100 parts by weight) and the above-mentioned hardener R3 (28 parts by weight) were uniformly mixed to prepare the undercoat material 2-9. The properties of this undercoat material 2-9 are shown in Table 2.

[0142] (Undercoat material 2-10) The above-mentioned base agent Q6 (100 parts by weight) and the above-mentioned hardener R3 (17 parts by weight) were uniformly mixed to prepare the undercoat material 2-10. The characteristic values ​​of this undercoat material 2-10 are as shown in Table 2.

[0143] (Undercoating material 2-11) The above-mentioned base agent Q7 (100 parts by weight) and the above-mentioned hardener R3 (28 parts by weight) were uniformly mixed to prepare the undercoat material 2-11. The properties of this undercoat material 2-11 are shown in Table 2.

[0144] (Undercoat material 2-12) The above-mentioned base agent Q8 (100 parts by weight) and the above-mentioned hardener R4 (20 parts by weight) were uniformly mixed to prepare the undercoat material 2-12. The properties of this undercoat material 2-12 are shown in Table 2.

[0145] (Undercoat material 2-13) The above-mentioned base agent Q8 (100 parts by weight) and the above-mentioned hardener R5 (10 parts by weight) were uniformly mixed to prepare the undercoat material 2-13. The properties of this undercoat material 2-13 are shown in Table 2.

[0146] (Test Examples 2-1 to 2-13) Except for using primers 2-1 to 2-13 instead of primer 1-1, test specimens were prepared and tested in the same manner as in Test Example 1-1. The test results are shown in Table 3. Among these, for Test Examples 2-1 to 2-8, 2-12, and 2-13 (corresponding to Examples), the color tone of the primer coating was different from the color tone of the existing wall surface, and it was easy to confirm that the primer coating was formed evenly over the entire uneven pattern of the existing wall surface, and the results were generally better than those of Test Examples 2-9, 2-10, and 2-11 (corresponding to Comparative Examples).

[0147] [Table 2]

[0148]

Table 3

Claims

1. A decorative method for existing walls that have deteriorated over time, comprising the steps of: The existing wall surface has an uneven pattern on its surface. The present invention provides a method for manufacturing a steel sheet having an existing coating film, the method comprising the steps of: providing an existing coating film of at least one type selected from an inorganic coating film, an organic-inorganic composite coating film, and a fluororesin coating film; For the above existing wall, The composition comprises a resin component, and a powder (m) having an average particle diameter of 1 μm or less and / or a powder (n) having an oil absorption of 100 ml / 100 g or more and an average particle diameter of 2 to 100 μm, the resin component includes a compound having a reactive silyl group, the compound having a reactive silyl group being one or more selected from a tetraalkoxysilane compound, an alkylalkoxysilane compound, and a silane coupling agent; The powder (n) is one or more selected from zeolite, sodium sulfate, alumina, allophane, diatomaceous earth, hydrous silicon dioxide, vermiculite, perlite, Oya stone powder, activated clay, charcoal, activated carbon, wood powder, and shirasu balloon; The total amount of the powder (m) and the powder (n) is 10 to 250 parts by weight per 100 parts by weight of the solid content of the resin component, and a pigment volume concentration of 1 to 30% is applied as a base coat material, and after the coating is dried, a top coat material is applied. This is a cosmetic method characterized by the above. The oil absorption amount is a value measured by the method of JIS K5101-13-1:2004 "Refined linseed oil method".

2. 2. The decorative method according to claim 1, wherein the existing wall surface is constituted by a plurality of plate-shaped wall materials having an uneven pattern on a surface and an existing coating.

Citation Information

Patent Citations

  • Method for renovating external wall of building

    JP2006021116A

  • Covering product

    JP2012082406A

  • Decorative method

    JP2015051429A

  • Decorating method

    JP2015071160A

  • Two-liquid type primer composition

    JP2016117795A